Land Capability Classification of Ollukara Block Panchayat Using GIS. (2016) - Mary Silpa, T.J.; Nowshaja, P.T.
Abstract: Ollukara Block Panchayat in Thrissur district, which has depletion of ground water level, is selected for the study. Land is classified into land capability classes as per IS 6748(Part-1) for the purpose of watershed management. The result shows that the area comprises of five capability classes, II, III, IV, VI and VII. In these classes, class VI and VII are not suitable for agriculture. Class II, III, and IV are suitable for agriculture. Class III comprises 28.35% of the area. The area is presently under semi critical zone based on ground water level. Proper care should be given to the study area in terms of watershed management, since the area is only marginally away from over exploited category.